Analysis of Assistance Strategy for Halal Product Process (PPH) Self Declare Line in Micro and Small Enterprises (UMK) in Jambi Province (Case Study of Halal Product Process Companion (PPH)) - Rahma Nurdinia; Lucky Enggrani Fitri; Ridhwan . (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2023)
This study aims to determine strategies that can be applied in Halal Product Process Assistance (PPH) in the Self Declare in UMK line in Jambi Province. The research method used is qualitative descriptive research with data collection procedures through observation, interviews, and documentation and using SWOT Matrix as an analysis technique. The results showed the Halal Product Process Assistance Strategy (PPH) by knowing and comparing strengths, weaknesses, opportunities and threats that four created PPH Companion strategies in Halal Product Process Assistance (PPH) in the Self declare for UMK in Jambi Province, namely: (1) SO Strategy (Strenghts-Opportunities) PPH carries out its role actively and maintains good and informative services to UMK in the implementation of Process Assistance Halal Products (PPH), (2) WO (Weakness-Opportunities) Strategy Optimizing the role of PPH companions by strengthening knowledge and abilities regarding Halal Certification in the self-declare path as well as motivation and encouragement by LP3H, (3) ST Strategy (Strenght-Threat) BPJPH, Jambi Province Satgas Halal, and LP3H as well as PPH companions provide information to the public about the defense of halal certification obligations in 2024 and accommodate all related institutions and (4) the WT (Weakness-Threat) Strategy by strengthening the quality of PPH Companions in carrying out their roles by providing supporting facilities in the implementation of Halal Product Process Assistance (PPH) from BPJPH, Satgas Halal, LP3H. Keywords: Strategy, Halal Product Process Assistance (PPH), PPH Companion, Self Declare.